'Artificial spermatid'-mediated genome editing. Issue 3 (11th May 2019) - Wang, Lingbo; Li, Jinsong
Abstract: For years, extensive efforts have been made to use mammalian sperm as the mediator to generate genetically modified animals; however, the strategy of sperm-mediated gene transfer (SMGT) is unable to produce stable and diversified modifications in descendants. Recently, haploid embryonic stem cells (haESCs) have been successfully derived from haploid embryos carrying the genome of highly specialized gametes, and can stably maintain haploidy (through periodic cell sorting based on DNA quantity) and both self-renewal and pluripotency in long-term cell culture. In particular, haESCs derived from androgenetic haploid blastocysts (AG-haESCs), carrying only the sperm genome, can support the generation of live mice (semi-cloned, SC mice) through oocyte injection. Remarkably, after removal of the imprinted control regions H19 -DMR (differentially methylated region of DNA) and IG -DMR in AG-haESCs, the double knockout (DKO)-AG-haESCs can stably produce SC animals with high efficiency, and so can serve as a sperm equivalent. Importantly, DKO-AG-haESCs can be used for multiple rounds of gene modifications in vitro, followed by efficient generation of live and fertile mice with the expected genetic traits. Thus, DKO-AG-haESCs (referred to as 'artificial spermatids') combed with CRISPR-Cas technology can be used as the genetically tractable fertilization agent, to efficiently create genetically modified offspring, and is a versatile genetic tool for in vivo analyses of gene function.